A grapevine cytochrome P450 generates the precursor of wine lactone, a key odorant in wine. Issue 1 (25th August 2016) - Ilc, Tina; Halter, David; Miesch, Laurence; Lauvoisard, Florian; Kriegshauser, Lucie; Ilg, Andrea; Baltenweck, Raymonde; Hugueney, Philippe; Werck‐Reichhart, Danièle; Duchêne, Eric; Navrot, Nicolas
Summary: Monoterpenes are important constituents of the aromas of food and beverages, including wine. Among monoterpenes in wines, wine lactone has the most potent odor. It was proposed to form via acid‐catalyzed cyclization of ( E )‐8‐carboxylinalool during wine maturation. It only reaches very low concentrations in wine but its extremely low odor detection threshold makes it an important aroma compound. Using LC‐MS/MS, we show here that the ( E )‐8‐carboxylinalool content in wines correlates with their wine lactone content and estimate the kinetic constant for the very slow formation of wine lactone from ( E )‐8‐carboxylinalool. We show that ( E )‐8‐carboxylinalool is accumulated as a glycoside in grape ( Vitis vinifera ) berries and that one of the cytochrome P450 enzymes most highly expressed in maturing berries, CYP76F14, efficiently oxidizes linalool to ( E )‐8‐carboxylinalool. Our analysis of ( E )‐8‐carboxylinalool in Riesling × Gewurztraminer grapevine progeny established that the CYP76F14 gene co‐locates with a quantitative trait locus for ( E )‐8‐carboxylinalool content in grape berries. Our data support the role of CYP76F14 as the major ( E )‐8‐carboxylinalool synthase in grape berries and the role of ( E )‐8‐carboxylinalool as a precursor to wine lactone in wine, providing new insights into wine and grape aroma metabolism, and new methods for food and aroma research and production.